Effect of orthodontic debonding and residual adhesive removal on 3D enamel microroughness - Joanna Janiszewska-Olszowska; Robert Tomkowski; Katarzyna Tandecka; Piotr Stepien; Tomasz Szatkiewicz; Katarzyna Sporniak-Tutak; Katarzyna Grocholewicz (PeerJ, 2016)
Background Termination of fixed orthodontic treatment is associated with bracket debonding and residual adhesive removal. These procedures increase enamel roughness to a degree that should depend on the tool used. Enamel roughening may be associated with bacterial retention and staining. However, a very limited data exists on the alteration of 3D enamel roughness resulting from the use of different tools for orthodontic clean-up. Aims 1. To perform a precise assessment of 3D enamel surface roughness resulting from residual adhesive removal following orthodontic debonding molar tubes. 2. To compare enamel surfaces resulting from the use of tungsten carbide bur, a one-step polisher and finisher and Adhesive Residue Remover. Material and Methods Buccal surfaces of forty-five extracted human third molars were analysed using a confocal laser microscope at the magnification of 1080× and 3D roughness parameters were calculated. After 20 s etching, molar tubes were bonded, the teeth were stored in 0.9% saline solution for 24 hours and debonded. Residual adhesive was removed using in fifteen specimen each: a twelve-fluted tungsten carbide bur, a one-step finisher and polisher and Adhesive Residue Remover. Then, surface roughness analysis was repeated. Data normality was assessed using Shapiro–Wilk test. Analysis of variance (ANOVA) was used to compare between variables of normal distribution and for the latter—Kruskal-Wallis test. Results Sa (arithmetical mean height) was significantly different between the groups (p = 0, 01326); the smoothest and most repeatable surfaces were achieved using Adhesive Residue Remover. Similarly, Sq (root mean square height of the scale-limited surface) had the lowest and most homogenous values for Adhesive Residue Remover (p = 0, 01108). Sz (maximum height of the scale-limited surface) was statistically different between the groups (p = 0, 0327), however no statistically significant differences were found concerning Ssk (skewness of the scale-limited surface). Discussion Confocal laser microscopy allowed 3D surface analysis of enamel surface, avoiding the limitations of contact profilometry. Tungsten carbide burs are the most popular adhesive removing tools, however, the results of the present study indicate, that a one step polisher and finisher as well as Adhesive Residue Remover are less detrimental to the enamel. This is in agreement with a recent study based on direct 3D scanning enamel surface. It proved, that a one-step finisher and polisher as well as Adhesive Residue Remover are characterized by a similar effectiveness in removing residual remnants as tungsten carbide bur, but they remove significantly less enamel. Conclusion Orthodontic debonding and removal of adhesive remnants increases enamel roughness. The smoothest surfaces were achieved using Adhesive Residue Remover, and the roughest using tungsten carbide bur.